Perancangan Vidio Dokumenter Tarian Lukah Gilo - Maharian Agung; Dendra Rama Yusuf (Iam-Indonesia, 2024)
The Lukah Gilo dance is a dance that requires supernatural or magical powers. This dance uses lukah (bubu) as its main property. The term Lukah Gilo comes from two words, namely Luka (bubu), which is an oval-shaped fish or eel catching tool made from woven sticks or rattan, while Gilo is the Minang word for "crazy". The meaning of gilo in this dance is a lukah that can move everywhere and its movements are uncontrolled after the lukah is recited by a mantra by the kulipah.A method is a work system to facilitate the implementation of an activity to achieve a specified goal. The method used in this design is 5W+1H analysis. The design of this Lukah Gilo Dance documentary video will be 7 minutes 16 seconds long and will feature a dance from fish catchers (bubu), a supernatural dance, featuring speakers who will tell the history of the Lukah Gilo Dance, made based on factual stories from observations and interviews.